Nonrenewable Resources – the Gateway Towards a Solar Era - Alexandra Mihaela Constantin (CES Working Papers, 2011)
The end of the 20th century was preserving and handing down the concept of economic growth as the main goal of most of the governments and economic advisers, even if the world was integrating in a mondialist system. This economic model lasted for a long time, but it will not survive the 21st century, when the development of nations will depend increasingly on the security of natural resources. Progress now depends on a much more profound economic transformation than it has been possible so far, especially since countries around the world rely on the availability of renewable and nonrenewable resources to meet their rising needs and expectations. The transition from the traditional economic paradigm to that based on the sustainable or ecological economy takes years of changes at all levels – from theory to practice. The aim of this paper is to introduce the progressive visions of some outstanding specialists who have looked for solutions to make a sustainable economy possible. The transition to a world sustainable economy implies admitting the fact that human economy is just a part of the global ecosystem which encompasses it.
Keywords: 330; nonrenewable resources; renewable resources; solar technologies; sustainable development